Hubungan Durasi Penggunaan Gawai dengan Perilaku Prososial Anak - Taufik, Nabila Azzahra; Nasirun, M.; Wembrayarli, Wembrayarli; Suryadi, Didik; Agustriana, Nesna (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2024)
The phenomenon of gadget use in early childhood reaps polemic regarding its impact on children’s development, one of which is in the social aspect. Allegedly the use of gadgets for a particular duration can affect the social development of children. This study aims to describe the correlation between the gadget use duration to group b children’s prosocial behavior in Early Childhood Education Segugus Kembang Sepatu. From the population of 141 children, this study uses only 35 children using stratified random sampling. The data were collected using a questionnaire. Furthermore, the analysis technique used in this study is Pearson product-moment. The results showed that the average duration of gadgets used for group b children of Early Childhood Education Segugus Kembang Sepatu was 1-2 hours/day, and prosocial behavior was Very High. The hypothesis test showed no significant correlation between gadget use duration and group b children’s prosocial behavior in Early Childhood Education Segugus Kembang Sepatu.